2018
DOI: 10.1159/000485972
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib for Anaplastic Thyroid Cancer and Lenvatinib-Induced Thyroid Dysfunction

Abstract: Background: Lenvatinib is an oral multitargeted tyrosine kinase inhibitor that has an anticancer action in patients with differentiated thyroid cancer that is refractory to radioiodine. Knowledge of the efficacy and safety of lenvatinib in patients with anaplastic thyroid cancer (ATC) is limited. Tyrosine kinase inhibitors frequently cause hypothyroidism, but the incidence of hypothyroidism with lenvatinib is unclear. Objectives: We conducted a retrospective study to investigate the efficacy and safety of lenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
4
22
0
1
Order By: Relevance
“…The different types of cancers like RAI-refractory DTC, MTC, and ATC show a diversity in outcomes. Not surprisingly, ATC shows the worst survival rates, with an OS of 165 days [44] and 166 days [33] and a PFS of 7.4 months [49]. These results support the current knowledge regarding ATC having a much worse prognosis compared to the other types of thyroid cancer, even when treated with MKIs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The different types of cancers like RAI-refractory DTC, MTC, and ATC show a diversity in outcomes. Not surprisingly, ATC shows the worst survival rates, with an OS of 165 days [44] and 166 days [33] and a PFS of 7.4 months [49]. These results support the current knowledge regarding ATC having a much worse prognosis compared to the other types of thyroid cancer, even when treated with MKIs.…”
Section: Discussionsupporting
confidence: 79%
“…Three studies investigated the effect of lenvatinib in patients with ATC: Takahashi et al [49] measured a PFS of 7.4 months. Koyama et al [44] reported an OS of 165 days and an RR of 60%. Moreover, Iwasaki et al [33] published an OS of 166 days and an RR of 17.4%.…”
Section: Resultsmentioning
confidence: 99%
“…Retrospective data can be used to bridge the current knowledge gap, and provide much-needed data for clinicians looking to improve outcomes for their patients. Previous retrospective analyses in Japanese patients have indicated that lenvatinib is associated with disease control rates (clinical response or stable disease) of 44% ( 21 ) to 100% ( 22 ), and OS times of 165 ( 22 ) to 166 ( 21 ) days, although tumor volumes were not evaluated. While it is not possible to directly compare studies due to the heterogeneity of the enrolled patients and the differing therapeutic procedures used, the treatment regimen used in our institute was able to produce a relatively lengthy median OS of 230 days, and additionally demonstrated a direct, measurable impact on tumor volume in almost 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of ATC patients treated with Lenvatinib resulted in partial responses (PR) in 60% (3/5) of patients whereas 40% (2/5) experienced stable disease with manageable toxicity. In addition, the observed objective response rate (ORR) was 60% with median time to progression (TTP) and overall survival (OS) as 88 and 165 days respectively [ 30 ].…”
Section: Current Therapeutic Regimesmentioning
confidence: 99%